The Influence of Capital Expenditure and Employee Expenditure on the Education Index through Employment Absorption and Poverty in Regencies/Municipalities of Jambi Province - Qodri, Muhammad; Tanjung, Hendri; Huda, Nurul; Nurhayati, Immas (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2026)
The purpose of this study is to examine how capital expenditure (X1) and employee expenditure (X2) influence the education index of regencies/municipalities (Y2) through employment absorption (Z1) and poverty (Z2) during the period 2002–2024. The method applied is multiple linear regression using the selected Random Effects Model (REM), with data analysis conducted through Eviews 8.0 Series to process panel data. The results of the t-test show that among the examined variables (capital expenditure (X1), employee expenditure (X2), employment (Z1), and poverty (Z2)), only capital expenditure (X1) does not have a significant effect on the education index of regencies/municipalities in Jambi Province (Y2) during 2002–2024, with a significance level of 5%. The other three variables—employee expenditure (X2), employment (Z1), and poverty (Z2)—were found to have a significant impact on the education index within the same period, at the 5% significance level. The Adjusted R-Squared value of 0.799658 (lower than the fixed effect model’s 0.900323) indicates a high R-Squared value of 0.803492. The F-statistic probability of 0.000000 further confirms the model’s overall significance, although the Durbin-Watson statistic of 0.242935, which falls below 2, suggests potential autocorrelation issues.